2020
DOI: 10.31557/apjcp.2020.21.2.465
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Serum CoQ10 Levels and other Antioxidant Markers in Breast Cancer

Abstract: It can make an impact on the different stages of cancer development (Jomova and Valko, 2011). It can alter the DNA sequence in the initiation step, increase cell division/ reduce apoptosis in the promotion stage and can also promote additional changes to the DNA in the progression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Studies on the use of serum survivin levels as a diagnostic marker have shown that patients with hepatocellular carcinoma and acute lymphoblastic leukemia have higher serum survivin levels than healthy individuals. [27–30] However, in contrast to these studies, some studies in patients with lung cancer did not show a significant increase in serum survivin levels. [28,66] Since the aim of our study was to examine the relationship between survivin levels, survival, and response to treatment in patients with MPC, survivin was not evaluated as an early diagnosis marker.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Studies on the use of serum survivin levels as a diagnostic marker have shown that patients with hepatocellular carcinoma and acute lymphoblastic leukemia have higher serum survivin levels than healthy individuals. [27–30] However, in contrast to these studies, some studies in patients with lung cancer did not show a significant increase in serum survivin levels. [28,66] Since the aim of our study was to examine the relationship between survivin levels, survival, and response to treatment in patients with MPC, survivin was not evaluated as an early diagnosis marker.…”
Section: Discussionmentioning
confidence: 92%
“…From this point of view, survivin levels may also have diagnostic value . [27][28][29][30] Following determining the serum levels of basal survivin in patients with metastatic pancreatic cancer (MPC), we analyzed the correlations between this level and the clinicopathological features of the patients in our study. We also investigated the relationships between the survivin level with prognosis and treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…It is caused by complex, interconnected risk factors. One of the most important factors is the genetic and epigenetic factors (El-Attar et al, 2020). The progression of BC depends on intrinsic factors related to the tumor cells, such as transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is a benzoquinone containing a 50-carbon isoprenoid side chain with ten isoprenyl units in its side chain. Its solubility in water is very low (0.7 ng/mL) due to its high molecular weight (863) and high lipophilicity [12]. Ubiquinone is an essential cofactor in the production of ATP during oxidative phosphorylation.…”
Section: Introductionmentioning
confidence: 99%